CRITICAL ANALYSIS OF BANTU EDUCATION ACT OF 1953 AND IMPLICATIONS ON COVID-19 PANDEMIC IN BLACK SCHOOLS: A SOCIAL JUSTICE PERSPECTIVE - Shuti Steph Khumalo (Universitas PGRI Madiun, 2022)
Corona Virus Disease (COVID-19) caught the world education systems by surprise and inflicted a deep-felt disruption in the previously disadvantaged black schools in South Africa. Even before the outbreak of the pandemic, the previously disadvantaged black South Africans schools experienced an educational resource backlog. These challenges dates back from the days of apartheid where Hendrick Verwoerd, the then minister of native affairs promulgated the Bantu Education Act of 1953 where the provision of substandard education for black people was officialized. This Act was based on the assumption that blacks are inferior in society and thus have to receive an education system which is second-rate. The aim of this conceptual argument is to present the critical and analytical association between the ramifications of the Bantu Education Act of 1953 on the provision of educational resources and the outbreak of COVID-19 pandemic in the previously sidelined black schools. This paper is a conceptual argument and draws from a plethora of extant literature and is undergirded by theory of social justice as advocated by John Rawls. Further the paper also locates its thesis from Nancy Frasers’ conceptions of social justice. This study is crucial in contributing to the body of knowledge on the provision of educational resources in schools and in particular-conscientize relevant education authorizes in the South African context to seriously address educational backlog in previously disadvantaged black schools.